Eastern Feminism? Some Considerations on Women and Religion in a Post-Communist Context (Romania, Hungary) - Bodó, Márta (Feminist theology, 2015)
In the context of mainstream feminism(s), Eastern-European women, coming from a post-Communist context are overwhelmed. As they have been unable to access the newest developments of feminist thought, feminist theology, they cannot find their own place and voice. In order to overcome this state of mind, this article puts forward an approach and a strategy. Drawing from the main ideas of contemporary Romanian and Transylvanian feminists – Mihaela Mudure, Mihaela Miroiu, Réka Geambasu, Enikő Magyari-Vincze and others – the article aims to start the quest for a fitting Eastern European-type of feminism. Post-Communist countries are the so-called ‘second world’. They need to find their own way, their own voice, similar to the ‘third world’, which has already started to do so. The knowledge and reception of the international feminist movement and its main oeuvre can help Central and Eastern European women theologians find those aspects that have supported others. Stating the specific situation of ‘second world’ women and seeking the theological aspects that describe their position and problems adequately, they can contribute to finding their one and only special voice.